Psoriatic Arthritis during Treatment with Bevacizumab for Anaplastic Oligodendroglioma. (29th November 2012) - Graceffa, D.; Maiani, E.; Pace, A.; Solivetti, F. M.; Elia, F.; De Mutiis, C.; Bonifati, C.
Abstract : Bevacizumab is a recombinant humanised monoclonal antibody directed against the vascular endothelial growth factor (VEGF). The drug, alone or in combination with other anticancer agents, has been shown to be effective against several types of neoplasms. We report a case of a woman with a history of severe psoriasis who developed psoriatic arthritis during a course of bevacizumab, which was administered for a malignant glioma.